Temperature invariant high dielectric properties over the range 200 °C–500 °C in BiFeO3 based ceramics. Issue 4 (April 2018) - Malik, Rizwan Ahmed; Zaman, Arif; Hussain, Ali; Maqbool, Adnan; Song, Tae Kwon; Kim, Won-Jeong; Sung, Yeon Soo; Kim, Myong-Ho
Abstract: Lead free piezoelectric ceramics (1– x ) (0.67Bi1.05 FeO3 –0.33BaTiO3 )– x LiNbO3 with x = 0.00, 0.015 and 0.030 were prepared by using conventional mixed oxide route. The incorporation of LiNbO3 into BF–BT system caused no significant change in crystal structure. However, an obvious variation in electrical properties was observed. The x = 0.015 composition showed enhanced ferroelectric and electric field-induced strain properties with dynamic piezoelectric constant S max / E max = 440 pm/V at a relatively low field of 40 kV/cm, along with a high working temperature upto T m = 392 °C. LiNbO3 addition improved the temperature insensitivity of relative permittivity (εr ) at high temperatures. At x = 0.030, a near-plateau εr ∼5000, extended across the temperature range, 200 °C–500 °C was observed which is advantageous for temperature insensitive dielectric ceramics for high temperature capacitor applications. Large strain and almost temperature invariant εr with high working temperature range makes this system suitable for high temperature electronic devices.